Virtual classrooms as a strategy to improve the English Language acquisition of students of the computing faculty belonging to Universidad Católica de Cuenca during the term october december 2010 - Vizñay Durán, Jenny Karina (2012)
This research project has been totally developed by following the steps proposed in the scheme of Army Polytechnic School Language. By means of this study, it is shown the results obtained at using virtual classrooms as a strategy in the English Learning Process, which was applied at ¿Universidad Católica de Cuenca¿ during the term October-December 2010. At the beginning of the development of this project, the first task was the situation analysis; it means the level in which the students were respect to the knowledge about English basic grammar structures. After that some virtual classrooms were designed according to the situation found in the test given to the students where I determined some faults in the learning, especially in grammar structures. The theoretical frame has as base line, books about teaching-learning process, internet and some compiled texts I had used in previous studies. A descriptive methodology has been used to explain the hypothesis I have stated based on the advantages of the use of virtual classrooms, which can be considered as crucial at the moment a student is exposed to a target language. By doing so they can learn in a natural way like our mother tongue was acquired when we were children in direct contact with the life situations. That is the way how virtual classrooms interact directly with our senses. By means of a statistical analysis and interpretation of results we will see in a graphical way the results of this research for getting the idea easily. Finally, it is shown the positive results of this research like a summary in the conclusions; recommendations are made too, to complete this project.